Development of a two-stage Lau-Wan Wankel pump/mixer. Issue 2 (April 2016) - Lim, BY; Lau, MWS; Wan, S; Leong, J; Lim, A; Huo, D; Goh, KL
A two-stage Wankel pump/mixer device has been designed and prototyped as part of a final-year undergraduate project. Based on the concept of the Wankel rotary engine, the device features a 'two-apex' rotor instead of the conventional 'three-apex' rotor. The novelty of the device addresses a unique axis of rotation for the rotor, driven by a crankshaft. In particular, in order for the motion of the rotor to exhibit a trajectory to consistency with an epitrochoid, the rotational motion is guided by the linear motion of a pin sliding along a groove within the rotor; this novel linear-to-rotational motion approach is known as the Lau-Wan design. The feasibility of the Lau-Wan design has been demonstrated in an earlier project. Here, the prototype comprises two Lau-Wan pump/mixers serially connected to form a two-stage system—the aim is to study the effectiveness of the mixing of fluids as the fluids flow from one stage to the other when both rotors are rotating 'in phase'. A simple drive system was implemented by (a) coupling the two crankshafts using a timing belt and (b) coupling a low-speed motor to one of the two stages using a timing belt. Experiment was conducted to analyze the flow pattern of liquids in both stages using two types of liquid with different colors (and a slight variation in the viscosity). The flow pattern within the chamber of the first stage shows somewhat similar mixing patterns to those predicted by computational fluid models. We note that (1) the extent of drawing the fluid into the chamber, followed by compressing the fluid, depends on the rotor position, (2) laminar flow dominates the flow pattern during the suction and compressive actions of the rotor but micro-turbulence occurs in the regions adjacent to the rotor, (3) when the rotor rotates, the number of laminar layers somewhat increases with time. On the other hand, the second stage appears to be very efficient at drawing one of the two fluids; this may be attributed to the viscosity of the fluids. Within the limitations of the preliminary design, these characteristics suggest that the prototype exhibits a positive displacement pumping action, as well as mixing action.